The Ammatoa Traditional Village Government System in Organizing Indigenous Peoples at Kajang District Bulukumba Regency - Fadli Hidayat; Muh. Nur Yamin (dialektika kontemporer, 2021)
This study aims to find out how the Ammatoa Traditional Village government system in managing indigenous peoples in Kajang District, Bulukumba Regency. This type of research is descriptive qualitative with data collection techniques were carried out by interviews, observation and documentation. The technique of data analysis are using domain analysis, taxonomic analysis, componential analysis and cultural themes. The results show that the Ammatoa Traditional Village government system in structuring indigenous peoples by using pairs of ri kajang as regulations, customary law and as a guide in the life of indigenous peoples is still effective in structuring indigenous peoples, and with the existence of regional regulations number 9 of 2015 about concerning inauguration, recognition of rights and protection of rights that strengthen protection in the arrangement of indigenous peoples. The inhibiting factor in managing indigenous peoples is the existence of pressure from people outside the customary area who have begun to enter by bringing modernization and social changes that has begun to affect the Ammatoa indigenous people.